Etiologia, perfil de sensibilidade aos antimicrobianos e aspectos epidemiológicos na otite canina: estudo retrospectivo de 616 casos - de Oliveira, Veronica Baldim [UNESP]; Ribeiro, Márcio Garcia [UNESP]; da Silva Almeida, Ariani Cristina [UNESP]; Paes, Antonio Carlos [UNESP]; Zeni Condas, Larissa Anuska [UNESP]; Batista Lara, Gustavo Henrique [UNESP]; Junqueira Franco, Marilia Masello [UNESP]; Fernandes, Marta Catarina [UNESP]; Paganini Listoni, Fernando Jose [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
A retrospective study of etiology, antimicrobial susceptibility profile and multiple drug resistance, and major epidemiological aspects were investigated in 616 cases of canine otitis. Staphylococcus beta hemolitic (26.27%), Malassezia pachydermatis (12.35%), and Pseudomonas aeruginosa (8.8%) were the most common microorganisms identified. The isolates were susceptible mainly to norfloxacin (89.62%), gentamicin (83.25%), and ofloxacin (80.16%). High occurrence of resistance of isolates was observed to neomicin (30.84%) and cephalexin (27.63%). Multiple drug resistance to three or more and five or more of antimicrobials tested was observed in 34.9% and 15.5% of isolates, respectively. The cases of canine otitis occurred predominantly in first years of age, in mixed breeds animals, at autumn season. The presence of itch, bad smell, and secretion in ear conduct were the major signs observed at clinical examination.
Etiology, antimicrobial susceptibility profile and epidemiological aspects in canine otitis: a retrospective study of 616 cases
Keywords: Otitis; dog; etiology; antimicrobial susceptibility; epidemiology